Deforestation processes in the livestock territory of La Vía Láctea, Matagalpa, Nicaragua. Issue 3 (4th May 2019) - Tobar-López, Diego; Bonin, Muriel; Andrade, Hernán J.; Pulido, Astrid; Ibrahim, Muhammad
ABSTRACT: Land-use change is considered one of the main causes of environmental degradation. Thus, its analysis will allow stakeholders to make reasonable decisions for land management. The objective of the present study was to understand the patterns of land-use/land-cover change and deforestation in a territory of importance for livestock development in Nicaragua: La Vía Láctea. The methodology was based on the digital processing of satellite images using the geographic information system that allowed the generation of the thematic cartography of land-use/land-cover for 1978, 1986, 1998, and 2011. Between 1978 and 2011, a total of 93% of the forest cover was converted to pasture for livestock development; this change has been influenced by socio-economic and political factors. This study, moreover, reinforces the idea that livestock is the main driver of deforestation. Landscape restoration requires increasing tree cover by adopting silvopastoral systems that improve biodiversity conservation and the provision of ecosystem services.